'Mindfulness Living with Insomnia': an mHealth intervention for individuals with insomnia in China: a study protocol of a randomised controlled trial. Issue 2 (15th February 2022) - Pan, Chen; Tie, Bingyu; Yuwen, Weichao; Su, Xiaoyou; Deng, Yunlong; Ma, Xin; Wu, Yan; Liao, Yanhui; Kong, Luya; Zhang, Yutao; Li, Ziwan; Pan, Qinghua; et al.
Abstract : Introduction: Insomnia has a remarkably negative effect on the work, quality of life and psychosomatic health of individuals, and imposes a substantial economic burden on society. Mindfulness-based interventions (MBIs) have proven beneficial in the treatment of insomnia. However, the effect of mobile or online-based (mHealth) MBIs requires further verification. This study will evaluate the effectiveness of an mHealth MBI, 'Mindful Living with Insomnia' (MLWI), relative to that of mHealth cognitive behavioural therapy for insomnia (CBT-I). Methods and analysis: The study is an mHealth, randomised controlled trial. Two hundred and fifty participants will be allocated randomly and equally to either the MLWI or CBT-I group. The intervention will involve 12 sessions over a 6-week course, with 2, 30 min sessions per week. The primary outcomes are sleep quality, severity of insomnia symptoms and sleep activity, according to the Pittsburgh Sleep Quality Index, Insomnia Severity Index and sleep tracker Mi Smart Band, respectively. The secondary outcomes are perceived stress, anxiety, depression and mindfulness. Outcomes will be evaluated at the baseline, end of the intervention period and at the 3-month follow-up. Data analyses will include covariance, regression analysis, χ 2, t-test and Pearson's correlations. Participants will be recruited from January to June 2022, or until the recruitment process is complete. The follow-up will be completed in December 2022. All trial results should be available by the end of December 2022. Ethics and dissemination: Full approval for this study has been obtained from the Ethics Committee at The Third Xiangya Hospital, Central South University, Changsha, China (21010). Study results will be disseminated via social media and peer-reviewed publications. Trial registration number: NCT04806009 .